Improvement Line Process to Reduce Production Cost Using Lean Six Sigma Approach (The Indonesian Journal of Business Administration, 2012)
According to the multidmensional economic crisis that impact on increasing drug prices, especially prices of patented drugs / trademark, these condition affect to the failure in fulfill of public health due to decreasing of purchase power. To cope these conditions required participation of the pharmaceutical industry especially in the manufacture to develop and socialize affordable drugs by all segments of civil society.This project aims to reduce the unit cost of products and that will directly affect the COGS product. Performed incrementally by selecting several products that provide the main value of PT. AAA. To analyze the causes and solutions to the problem, Six Sigma framework (DMAIC) was used which combined with the concept of Lean Manufacturing to eliminate non-value added processes called ―Lean Six Sigma